2017
DOI: 10.1016/j.bbrc.2017.10.056
|View full text |Cite
|
Sign up to set email alerts
|

The structure-activity relationship of ginsenosides on hypoxia-reoxygenation induced apoptosis of cardiomyocytes

Abstract: Ginsenosides have been studied extensively in recent years due to their therapeutic effects in cardiovascular diseases. While most studies examined the different ginsenosides individually, few studies compare the therapeutic effects among the different types. This study examined how effective protopanaxadiol, protopanaxatriol ginsenosides Rh2, Rg3, Rh1, and Rg2 of the ginsenoside family are in protecting H9c2 cardiomyocytes from damage caused by hypoxia/reoxygenation. In the current study, a model of myocardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 32 publications
(38 reference statements)
0
22
0
Order By: Relevance
“…Hypoxia/reoxygenation (H/r) injury, a mimic in vitro model of myocardial I/R injury, has been widely used to explore the underlying molecular mechanism of myocardial i/r injury (3)(4)(5). At present, a number of studies have explored myocardial H/R injury from the perspectives of the inflammatory response (6), cell apoptosis (7) and cell signal transduction (8), but the exact molecular mechanism remains unknown. Therefore, it is important to explore the potential molecular mechanisms of myocardial iri.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia/reoxygenation (H/r) injury, a mimic in vitro model of myocardial I/R injury, has been widely used to explore the underlying molecular mechanism of myocardial i/r injury (3)(4)(5). At present, a number of studies have explored myocardial H/R injury from the perspectives of the inflammatory response (6), cell apoptosis (7) and cell signal transduction (8), but the exact molecular mechanism remains unknown. Therefore, it is important to explore the potential molecular mechanisms of myocardial iri.…”
Section: Introductionmentioning
confidence: 99%
“…Most ginsenosides consist of a dammarane skeleton with 17 carbon atoms arranged in four rings. Due to the number of hydroxyl groups these compounds can be classified into two main categories: protopanaxadiol (PPD) and protopanaxatriol (PPT) [33].…”
Section: Bioactive Phytochemicals Of American Ginsengmentioning
confidence: 99%
“…Saponins are a very diverse group of plant metabolites, and many reports have indicated that their activity is affected by their structure, namely, by the nature of aglycone as well as the number and monosaccharide composition of sugar chains, which may be linear or branched (Chwalek, Lalun, Bobichon, Plé, & Voutquenne‐Nazabadioko, ; Feng et al, ; Vo et al, ). Most triterpene saponins are based on aglycone of the three most common types: dammarane, which is a tetracyclic structure, and two pentacyclic skeletons such as ursane and oleanane (Figure ), the latter of which is considered to be most abundant in nature.…”
Section: Structure–activity Relationship In Combined Therapymentioning
confidence: 99%